2015
DOI: 10.1075/ltba.38.2.09gaw
|View full text |Cite
|
Sign up to set email alerts
|

The reported speech evidential particle in Lamjung Yolmo

Abstract: Grammatically encoded evidentials that marks 'reported speech' , 'hearsay' or 'quotation' are attested in languages from a variety of families, but often receive cursory description. In this paper I give a detailed account of the reported speech particle ló in Lamjung Yolmo, a Tibeto-Burman language of Nepal. This particle is used when the speaker is reporting previously communicated information. This information may be translated from another language, may be a non-verbal interaction turn or may have been an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The name "Kyirong-Kagate" may have been appropriate several decades ago, when so little was known about the Yolmo language. The production of the Yolmo dictionary (Hari and Lama 2004) and an introductory grammar of the Melamchi dialect (Hari 2010), not to mention the observation of Yolmo speakers in Ilam (Thokar 2009) and work on the Lamjung variety (Gawne 2010(Gawne , 2011a(Gawne , 2011b(Gawne , 2013 means that there is now a great deal more published linguistic information about Yolmo, just as there is a great deal more anthropological work that has been done in the area.…”
Section: Verb Stemsmentioning
confidence: 99%
“…The name "Kyirong-Kagate" may have been appropriate several decades ago, when so little was known about the Yolmo language. The production of the Yolmo dictionary (Hari and Lama 2004) and an introductory grammar of the Melamchi dialect (Hari 2010), not to mention the observation of Yolmo speakers in Ilam (Thokar 2009) and work on the Lamjung variety (Gawne 2010(Gawne , 2011a(Gawne , 2011b(Gawne , 2013 means that there is now a great deal more published linguistic information about Yolmo, just as there is a great deal more anthropological work that has been done in the area.…”
Section: Verb Stemsmentioning
confidence: 99%
“…These findings provide a window into children's communicative competence with a syntactic system that requires reflection on others' knowledge and appropriate displays of internal states. Previous crosslinguistic studies of evidentiality in interaction (Dwyer, 2000 ; Gipper, 2011 ; Gawne, 2013 ; San Roque, 2015 ) found that adult speakers calibrate evidential marking to the expectations of their conversational partners. Research on children's uses of these syntactically embedded and polysemous grammatical systems can help demonstrate how children respond to cultural norms surrounding sociality, even when their uses of these systems are restricted in spontaneous talk.…”
Section: Discussionmentioning
confidence: 96%
“…Regardless of researchers' stances on the universal semantics of evidentiality, studies of the pragmatics of adult narratives note that evidentiality differentiates self/other perspectives (Mushin, 2001 ; Tournadre and LaPolla, 2014 , p. 241; DeLancey, 2018 ; Howard, 2018 ; Nuckolls, 2018 ). Several studies of evidentiality in adults' conversational sequences show that speakers choose evidential markers based on sensitivity to their interlocutors' perspectives (Dwyer, 2000 on Salar; Gipper, 2011 on Yurakare; Gawne, 2013 on Yolmo). In other words, speakers' uses of evidential morphemes demonstrate how they position their emotional and epistemic states in social contexts.…”
Section: Methodsmentioning
confidence: 99%
“…individuals in the recent past, and the lexical verb of saying having a broader distribution (Gawne 2015). Like other evidentials, the reported category marks source of information, but unlike other categories, this source of information in grounded in the speaker's interaction with previous discourse (Hengeveld & Hattnher 2015).…”
mentioning
confidence: 88%